The Neurocognitive Study for the Aging - Fofi Constantinidou (Dialogues in Clinical Neuroscience & Mental Health, 2018)
The Neurocognitive Study for the Aging (NEUROAGE) was formally established in 2009 with initial funding by the Cyprus Research Promotion Foundation. It is a longitudinal prospective project with a rolling admission process. NEUROAGE aims  to investigate cognitive processes such as memory, concentration, speed of information processing, language abilities and executive skills in a large sample of Cypriots (N > 800) who are native speakers of Greek (including the Cypriot-Greek dialect), with ages ranging from 45 through 90+. The project recruits community dwellers living independently who are assessed every two years.  In addition to the above general aims, NEUROAGE investigates the contribution of specific biological factors that may affect cognitive functions in adulthood including cardiovascular (e.g., metabolic syndrome, hyperlipidemia) and genetic markers (e.g., genetic polymorphisms including the apolipoprotein E4 allele). The project also aims to examine the relationship between quality of life, cognitive reserve, biological factors and cognitive functions. Finally, the specific study assesses the clinical efficacy of a cognitive rehabilitation program in both healthy adults and adults with mild cognitive impairment. Of additional scientific importance is that NEUROAGE has been able to recruit individuals with very little formal education, thus capturing the true effects of education on cognitive health, and investigate the interplay between education, health, and cognition.  It is stressed that this is the last generation of individuals with low education since following the establishment of the Republic of Cyprus in 1960, public education has been free and mandatory through grade 9 or age 15.